Scirtothrips menai sp.n., a new species from Costa Rica, Central America (Thysanoptera, Terebrantia, Thripidae) - Retana Salazar, Axel P. (2016)
The genus Scirtothrips Shull 1909 is characterized by small, pale, active thrips with no more than 1500 μm in length that feed generally on young leaves. Most species feed on a few host plants, while others are polyphagous, and they can be serious pests of a variety of unrelated economical crops. The new species described here has the interocellar setae in position 1/2, pmII longer than I and III and pronotal striae widely separated as in S. longipennis Bagnall 1909 and S. bounites Mound & Marullo 1996, but different in several other characters as the antennal pattern of colour, the head colour, the striae in vertex, the striae between ocelli, the striae in pronotum, the development of the tergal medial pair of setae and the number of rows of microthrichia in abdominal tergal lateral thirds.